Cover Image. Issue 5 (17th May 2019) - Navaratnam, Manchula; Maeda, Katsuhide; Hollander, Seth A.
Abstract : The cover image is based on the Educational Review Pediatric ventricular assist devices: Bridge to a new era of peri‐operative care by Manchula Navaratnam et al., https://doi.org/10.1111/pan.13609 .